How should core stability be evaluated? A comparison on integrated and isolated methods - Johansen, K.; Johnsen, M.; Seiler, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Lumbo-pelvic (core) stability and strength is determined by the integrated function of multiple deep and global muscles working in three dimensions. In contrast, the most popular quantitative tests of core function are one dimensional and isolated in nature. The purpose of this study was to compare the results of several common isolated muscle tests for the core region with results from two integrated, 3- dimensional "weak link" tests. Methods: 30 sports active females (18 ± 1 yrs, 167±7 cm, 60 ± 5 kg) who trained regularly (13 ± 5 hrs/wk) participating in the study. About 75% reported performing specific training for improved core stability. Between day test-retest reliability was evaluated for the one legged squat (pass-fail based on 90 degree hip angle and absence of inward knee rotation and/or adduction, 3 attempts) and a 30 degree leg abduction test from a supine bridge performed with one leg in an unstable sling hanging from the ceiling (pass-fail based on ability to maintain less than 2.5 degrees pelvic rotation with instrumented visual feedback). Subjects also performed a side bridge test to failure (holding time in s), a 60 degree isometric sit-up to failure (holding time), the Biering-Sørensen back extension test (holding time), and a 10 degree isometric hip abduction test (maximal force in N). Results: Combined right and left leg test-retest agreement for the one legged squat was 93%. Agreement for the supine 30 degree abduction test was 84%. 50% of the subjects failed the one legged squat test on one or both legs. 12 of 30 (40%) subjects failed the supine abduction test on one or both sides. Performance on the 4 isolated muscle tests was compared in 8 females who passed both left and right sides of the 2 integrated tests and 7 subjects who failed on at least 3 out of 4 side-specific tests. Biering-Sørensen (117 ± 47 vs 104 ±26 s, p=0.5), 60 degree flexion (206 ± 122 vs 215 ± 111 s, p= 0.89), side bridge (101 ± 27 vs 97 ±39, p= 0.82), and 10 degree abduction force (212 ± 32 vs 195 ± 49 N, p= 0.42) were all similar in the two groups. Conclusions: The 1-legged squat and 30 degree supine bridge abduction test both showed good test-retest agreement However, when clinical findings from these two functional tests were compared with results from 4 established muscle performance tests, we observed no relationship. Given the one-dimensional nature of the isolated muscle tests, we question their validity as integrated measures of lumbo-pelvic stability. We also observed that females who reported a combination of strength training exercises on stabile and unstable surfaces had fewer "weak links" based on functional testing.